)
4x+10x=28
у=2х
у=2х
14х=28
x=2
y=4
(2;4)
2u-v=3
10u=4
v=2u-3
u=0,4
v=0,8-3
u=0,4
v=-2,2
u=0,4
(0,4 ;-2,2)
p=3q+1
p^2-9q=7
p=3q+1
(3q+1)²-9q⇒ это можно в уме 9q+6q+1-9q=7
p=3q+1
6q=6
p=4
q=1
(4;1)
x=2z
y=z-3
2z+z-3+z=9
4z=12⇒z=3
y=3-3=0
x=3*2=6
(6;0;3)
#22222222222
a=3b
2b=34-5
2b=29
a=3*14,5
(b=14,5
a=43,5
(14,5; 43,5)
- q=2-3p⇒q=3p-2
5p-3*(3p-2)=-6
5p-9p+6=-6
q=3p-2
-4p=-12
q=3*3-2
p=3
q=7
(3;7)
u=1+2q
(u-2q)(u+2q)=5
u=1+2q
u+2q=5 ⇒2q+1+2q=5
u=1+2q
4q=4
u=1+2*1⇒u=3
q=1
(3;1)
z=4x
y=x+2
x+2*(x+2)-4x=3
x+2x+4-4x=3⇒ -x=-1
x=1
z=4
y=1+2=3
(1;3;4)
№1
а) y=2x
4x+5y=28
4x+10x=28
14x=28
x=2
y=2*2=4
(2;4)
б) 2u-v=3 = > v=2u-3
7u+3v=4
7u+6u-9=4
13u=13
u=1
v=2-3=-1
(1;-1)
в) p-3q=1 => p=3q+1
p^2-9q=7
(p-3q)(p+3q)=7
1*(p+3q)=7
p+3q=7
3q+1+3q=7
6q=6
q=1
p=3+1=4
(4;1)
г) x=2z
y-z+3=0 => y=z-3
x+y+z=9
2z+z-3+z=9
4z=12
z=3
y=3-3=0
x=3*2=6
(6;0;3)
№2
а) a=3b
5a+2b=34
15b+2b=34
17b=34
b=2
a=3*2=6
(6;2)
б) 3p-q=2 => q=3p-2
5p-3q=-6
5p-9p+6=-6
4p=12
p=3
q=9-2=7
(3;7)
в) u-2q=1 =>u=2q+1
u^2-4q=5
(u-2q)(u+2q)=5
1*(u+2q)=5
u+2q=5
2q+1+2q=5
4q=4
q=1
u=2+1=3
(3;1)
г) z=4x
y-x-2=0 => y=x+2
x+2y-z=3
x+2x+4-4x=3
x=1
z=4
y=1+2=3
(1;3;4)
Объяснение: